ANTIOXIDANT ACTIVITY OF HOT WATER SOLUBLE FRACTION FROM AGARICUSHETEROCYSTIS AND ITS EFFECT ON APPLE BROWNING - Jagadish, Loganathan K.; Hemalatha, M.; Gunasundari, D.; Shenbhagaraman, R.; Kaviyarasan, V. (Emirates Journal of Food and Agriculture, 2017)
The present was carried out to investigate the antioxidant activity of Agaricus heterocystis hot water extract and their effect on apple browning. Antioxidant activities were assayed spectrophotometrically against ABTS (2,2-Azino-bis(3-ethylbenzothiazoline-6- sulfonicacid) and DPPH (1,1-diphenyl-2-picrylhydrazyl) radicals. The mushroom extract showed an effective antioxidant activity against both ABTS and DPPH radicals with the EC50 value of 0.020±0.55 mg/ml and 6.42±0.261 mg/ml respectively. The extract inhibited the browning of fresh apple when analysed by immersing the sliced apple into the mushroom extract that prevented the browning development effectively when compared with the controls. These observations suggested that Agaricus heterocystis hot water soluble fraction contained certain antioxidant substance or compounds which inhibited the oxidation of endogenous compounds present in the apple.